National culture and innovation: a multidimensional analysis - Aline Espig; Igor Tairan Mazzini; Clarice Zimmermann; Luciano Castro da Carvalho (Innovation & Management Review, 2022)
Purpose - This study aims to examine the relationships between the different national culture dimensions presented by Hofstede and innovation data by country to analyze which characteristics of national culture dimensions contribute to the country becoming more innovative. Design/methodology/approach - The study is characterized as descriptive and quantitative, using multiple linear regression equations as data analysis technique. To carry out the analysis, this study made use of secondary data from Hofstede's national culture database, data on innovation indicators from the Global Innovation Index and population data from the World Bank database. The analysis comprises data from 2015 to 2018. Findings - National culture affects innovation rates positively. The most favorable situation to boost innovation is when there is a low distance from power, high individualism, femininity characteristics, low aversion to uncertainty, long-term orientation and a higher level of indulgence. Originality/value - The temporal analysis comprises a wider list of countries from all continents, which had not been considered in previous studies.
Keywords: 650; Innovation; National culture